ON 2-ABSORBING PRIMARY AND WEAKLY 2-ABSORBING ELEMENTS IN MULTIPLICATIVE LATTICES - (:unkn) unknown (FORUM EDITRICE UNIV UDINESE, 2015)
In this paper, we introduce the concept of 2-absorbing primary and weakly 2-absorbing primary elements which are generalizations of primary and weakly primary elements in multiplicative lattices. Let L be a multiplicative lattice. A proper element q of L is said to be a (weakly) 2-absorbing primary element of L if whenever a, b, c is an element of L with (0 not equal abc <= q) abc <= q implies either ab <= q or ac <= root q or bc <= root q. Some properties of 2-absorbing primary and weakly 2-absorbing primary elements are presented and relations among prime, primary, 2-absorbing, weakly 2-absorbing, 2-absorbing primary and weakly 2-absorbing primary elements are investigated. Furthermore, we determine 2-absorbing primary elements in some special lattices and give a new characterization for principal element domains in terms of 2-absorbing primary elements.
Keywords: prime element; primary element; 2-absorbing element; 2-absorbing primary element; multiplicative lattice; COMMUTATIVE RINGS; IDEALS